Individual Ability In Financial Literacy - Adriani; Murtiadi Awaluddin; Baso Sardjan; Sitti Fadjriyah; Indah Ramadhani Amir (CV. ULIL ALBAB CORP, 2024)
The aim of the research is to find out how to manage financial literacy using the Du Pont system method. The method used in this research is qualitative and quantitative research methods using the du pont method In measuring financial literacy Regarding ROA, ROE, and interest margins (and non-interest fees), all of them in financial operations for corporate success” (Sundarajan : 2022). Research result DuPont Model which is based on analysis of Return on Equity (ROE) & Return on Investment (ROI). The return on equity disaggregates performance into three components: Net Profit Margin, Total Asset Turnover, and the Equity Multiplier. Return on Investment consists of Assets Turnover and Profit Margin. The return on investment consists of Assets Turnover (Operating Income X Total Assets) and Profit Margin (EBIT X Operating Income). In conclusion, ROE & ROI is the most comprehensive measure of profitability of a firm. It considers the operating and investing decisions made as well as the financing and tax- related decisions